PERKEMBANGAN BAHASA ARAB PADA MASA DINASTI UMAYYAH DAN ABBASIYAH: SEBUAH PERBANDINGAN HISTORIS DAN LINGUISTIK - Anisa Tufahati; Ronaa Fitri Butsainah; Muhammad Afif Amrullah (Makkah: Journal Of Islamic Studies, 2025)
This journal analyzes the development of the Arabic language during two crucial periods in Islamic history: the Umayyad Dynasty (661–750 CE) and the Abbasid Dynasty (750–1258 CE). The study aims to identify the general characteristics, language policies, linguistic developments, and literary contributions of each period, as well as to compare them in order to highlight their fundamental differences and similarities. A historical-descriptive and comparative research method is employed by examining both primary and secondary literature. The findings indicate that the Umayyad Dynasty served as the foundation for the dominance of the Arabic language through administrative Arabization and the early stages of standardization, while the Abbasid Dynasty brought Arabic to the height of intellectual glory through a massive translation movement and the advancement of various sciences. Although their focuses differed—political-administrative in the Umayyad era and intellectual-scientific in the Abbasid era—their shared commitment to Arabic as the core of Islamic civilization remained a fundamental similarity. This journal provides a deeper understanding of the dynamic evolution of the Arabic language within the context of Islamic history and its relevance to linguistic and civilizational studies. Book Antiqua 10, single space.